Family Systems, Political systems, and Asia’s ‘Missing Girls’ : The Construction of Son Preference and Its Unraveling - Das Gupta, Monica (2012)
Son preference is known to be found in certain types of cultures, that is patrilineal cultures. But what explains the fact that China, South Korea, and Northwest India manifest such extreme child sex ratios compared with other patrilineal societies? This paper argues that what makes these societies unique is that their pre-modern political and administrative systems used patrilineages to organize and administer their citizens. The interplay of culture, state, and political processes generated uniquely rigid patriliny and son preference. The paper also argues that the advent of the modern state in these settings has unraveled the underpinnings of the rigid patrilineal rules, and unleashed a variety of forces that reduce son preference. Firstly, the modern state has powerful tools for incorporating and managing its citizenry, rendering patrilineages a threat rather than an asset for the state. Secondly, the modern state has brought in political, social, and legal reforms aimed to challenge traditional social hierarchies, including the age and gender hierarchies of the kinship system. Thirdly, industrialization and urbanization have ushered in new modes of social organization, which reduce the hold of clans and lineages. Studies of the impact of the media suggest that states can accelerate the resultant decline in son preference, through media efforts to help parents perceive that daughters can now be as valuable as sons.